Dagital Dakwah Habib Husein Ja’far Al-Hadar dalam Konten Youtube Login (Analisis Teori Media Baru) - Hafidz Khoiril Muradho; Imam Mahdi; Moch Iqbal (Departement of Mathematics Education, 2024)
This study purpuse to analyze how Habib Husein Ja'far al Hadar uses digital technology as a medium for da'wah using new media communication theory. Today's increasingly advanced technological developments certainly add to the challenge for a preacher to think about how Islamic teachings can be accessed by many people. So the author is interested in researching the digitization of Habib Husein Ja'far al Hadar's preaching, an Indonesian citizen of Arab descent, increasingly famous through Deddy Corbuzier's YouTube channel in Login content as a medium used to spread the teachings of the Islamic religion. Inviting friends to discuss from various circles and backgrounds, different ethnicities and religions. The author found several important points that were conveyed by Habib Husein Ja'far al Hadar. First, Islam is a religion full of love and joy that is far from radical. Second, Islam teaches tolerance between religions. Third, convey the truth with good morals. These three things make Habib Husein Ja'far al Hadar loved by all levels of society. Means the use of the number bag media on mathematical learning has a moderate influence on the learning outcomes of pupils of class IV SDN 36 Pontianak Kota.